KRITIK SOSIAL PADA NOVEL Dilan : dia adalah Dilanku Tahun 1990 KARYA PIDI BAIQ - Naomi Natalia Pangaribuan; Netti Vera br Ginting; Rini Wulandari br Purba; Parsaoran Aritonang; Annisa Annisa (Jurnal Genre (Bahasa, Sastra, dan Pembelajarannya), 2019)
This research title is  SocialCriticism in the Novel "Dilan: dia adalah Dilanku Tahun 1990" by Pidi Baiq. The aim of this study is (1) To find out the social criticism contained in the novel, (2 ) To find out the results of the social criticism analysis contained in the novel. This research is included in library techniques and content analysis. The method used is descriptive qualitative research methods. Data sources used in this study is the text of the novel "Dilan: dia adalah Dilanku Tahun 1990" by Pidi Baiq, the second print in 2016 and published by Pastel Books Bandung. The study used a sociological literary approach that considered social aspects to better understand the social symptoms contained in the novel "Dilan: dia adalah Dilanku Tahun 1990" which focused on issues related to social criticism.The results of this study are aimed at the world of education, especially among adolescents who are still educated in schools which cause various  social problems that occur in the midst the environment of society. As for social criticism found in the novel " Dilan: dia adalah Dilanku Tahun 1990", that is social criticism of juvenile delinquency in school, criminalization, attitudes and behavior, educators (teachers), power, and injustice and low.